2020
DOI: 10.1371/journal.pone.0227374
|View full text |Cite
|
Sign up to set email alerts
|

Shock index and TIMI risk index as valuable prognostic tools in patients with acute coronary syndrome complicated by cardiogenic shock

Abstract: Background The aim of the study was to evaluate the usefulness of the shock index (SI) and the TIMI risk index (TRI Thrombolysis in Myocardial Infarction Risk Index) one hour after successful primary percutaneous coronary intervention (pPCI) for predicting in-hospital mortality in patients with acute coronary syndrome complicated by cardiogenic shock (CS). Methods Forty-seven consecutive patients with acute myocardial infarction (AMI) complicated by CS were included in this prospective observational study. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have used SI to predict mortality in the ACS population and have found that an increased SI can predict short-term mortality in patients with STEMI. A SI ≥0.7-0.8 on admission in patients with STEMI was associated with a mortality rate of 16-20%, and the lower the SI, the lower the risk of death (31)(32)(33)(34). This study showed that the traditional inflammatory indicators, WBC count and myocardial enzymes (LDH and AST), remain essential in the risk prediction of STEMI and confirmed that anemia might increase the risk among patients after PCI.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have used SI to predict mortality in the ACS population and have found that an increased SI can predict short-term mortality in patients with STEMI. A SI ≥0.7-0.8 on admission in patients with STEMI was associated with a mortality rate of 16-20%, and the lower the SI, the lower the risk of death (31)(32)(33)(34). This study showed that the traditional inflammatory indicators, WBC count and myocardial enzymes (LDH and AST), remain essential in the risk prediction of STEMI and confirmed that anemia might increase the risk among patients after PCI.…”
Section: Discussionsupporting
confidence: 58%
“…Prior studies have demonstrated the prognostic utility of SI in patients with individual cardiac pathologies, including ACS, heart failure, and cardiogenic shock [ 31 35 ]. SI alone was shown to perform as well as the GRACE risk score in patients with ACS, with the advantage of being easier to calculate [ 36 38 ]. Notably, both HR and SBP are included in the GRACE risk score [ 7 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure markedly increased mortality risk in ACS patients, as it reduced the cardiac output, diminished the oxygen perfusion into the lung circulatory and induced renin–angiotensin–aldosterone system activation 40. On the other hand, cardiogenic shock, as an indicator of end-organ hypoperfusion due to cardiac dysfunction, significantly increased the risk of mortality in ACS patients 41 42…”
Section: Discussionmentioning
confidence: 99%